Organochlorine pesticides accumulated by SPMD-based virtual organisms and feral fish in Three Gorges Reservoir, China. (July 2015) - Wang, Jingxian; Liang, Wei; Henkelmann, Bernhard; Pfister, Gerd; Schramm, Karl-Werner
Abstract: Organochlorine pesticides (OCPs) accumulated by semipermeable membrane device (SPMD) -based virtual organisms (VOs) and local feral fish were studied in Three Gorges Reservoir (TGR), China. VOs were deployed at seven sites in TGR for two periods in 2009 and 5 species of fish with different living habitats and feeding habits collected in the same periods from two counties in TGR. 28 OCPs were analyzed and the concentration and profile of OCPs in fish were quite different from those in VOs. The lipid-based concentrations of OCPs in fish ranged from 225.7 ng/g lw to 1996.4 ng/g lw which were much higher than those in VOs which ranged from 17.3 to 112.4 ng/g lw. Dichlorodiphenyltrichloroethanes (DDTs) were the prevalent OCPs in the investigated fish, while hexachlorobenzene (HCB) was the dominant compound in VOs. DDT in the few fish sample analyzed was not of concern based on chemical contaminant limits of non-carcinogenic effect. Highlights: OCPs contamination in fish was investigated in Three Gorges Reservoir, China. Comparison of OCPs accumulation was conducted in feral fish and VOs in TGR. Composition of OCPs in feral fish was significantly different from that in VOs. DDTs were the prevalent OCPs in fish and were mainly originated from historical usage. Abstract : Comparison of OCPs accumulation was conducted in feral fish and VOs in TGR.